The Moderating Role of Anxiety in the Relationship between Differentiation of Self and Filial Piety among Emerging Adults - Najwa Safira; Fikrotul Hanifah (Journal of Educational, Health and Community Psychology, 2026)
This study examined whether differentiation of self predicts filial piety among emerging adults and whether anxiety moderates this association. Using a quantitative cross-sectional design, we surveyed 261 participants via an online questionnaire assessing differentiation of self, anxiety, and filial piety. Data were analyzed using multiple linear regression and moderated regression. Differentiation of self was positively associated with filial piety (B = 0.595, p < .05), whereas anxiety was negatively associated with filial piety (B = −0.361, p < .05). The interaction between differentiation of self and anxiety was also positive and significant (B = 0.007, p < .05), supporting a moderating effect of anxiety. The final model accounted for 69.5% of the variance in filial piety, and the interaction term explained an additional 1.2% of variance. Simple slopes indicated that the positive association between differentiation of self and filial piety was stronger at higher levels of anxiety.